Presentation video analytics systems data in the form of heatmaps - S. G. Dobrodey; A. V. Borodulya (Системный анализ и прикладная информатика)
Describes the method of presentation video analytics data collected for continues time in the form of heatmaps for analysis of the movement of human flows in accumulation sites. The scene is divided into zones where objects are counted. The counting results are stored in the data store with a specified periodicity. The heat map is based on matrix of counters of objects in specific areas of the scene. Over the matrix, the normalization operation is performed and, depending on the value of the elements, the color of the heat map areas is assigned based on the linear color gradient.